2015
DOI: 10.1016/j.pmrj.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Prognostic Indices for Recovery of Physical Functioning Following Stroke: Part 2

Abstract: Functional recovery to physical grade VI can be predicted on the basis of patients' initial status after a stroke occurs and the type of rehabilitation services to be provided by using a simple scoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The results of a study by Pettersson et al indicates that powered wheelchairs mostly have a positive impact on the quality of life of patients with stroke [16]. But the role of AT in recovery from stroke seems be still underscored and is hard to validate, although walking/wheelchair use is regarded as significant sign of functional independence in post-stroke patients [17,18,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The results of a study by Pettersson et al indicates that powered wheelchairs mostly have a positive impact on the quality of life of patients with stroke [16]. But the role of AT in recovery from stroke seems be still underscored and is hard to validate, although walking/wheelchair use is regarded as significant sign of functional independence in post-stroke patients [17,18,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The second new observation is that balance impairment is closely related to independent performance on component activities of toileting. Previous studies have shown a relationship between the degree of impairment in TB and psychosomatic impairments . Di Monaco et al reported that balance is one of the most significant predictors of functional independence after stroke .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a relationship between difficulty in toileting and psychosomatic impairments including, paralysis, balance impairments and cognitive impairments . Therefore, the presence or absence of these impairments was also determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to many authors [5][6][7][8][9], only one in five patients completely recovers all movement of their upper limbs after a stroke. Poor recovery is often the result, not only of the sizes and localization of the poststroke foci, but of such diseases as diabetes mellitus, arterial hypertension, cardiovascular insufficiency, deep vein thrombosis of the legs, osteoporosis and epilepsy, and this considerably complicates the course of recovery and impairs the outcomes [10][11][12][13]. These factors present a difficult background that it is hard to modify in the acute and subsequent periods, however, there is also a second group of factors involved in limiting the effectiveness of rehabilitation and these can be partially corrected.…”
mentioning
confidence: 99%